Checklist of the genus Cortinarius in Romania: taxonomic and distributional insights - SZABÓ, Emerencia; DÉNES, Avar-Lehel; VERES, Róbert; DIMA, Bálint; KERESZTES, Lujza (Studia Universitatis Babeș-Bolyai Biologia, 2025)
The genus Cortinarius is one of the most diverse ectomycorrhizal lineages of Basidiomycota, yet its diversity in Romania has remained poorly documented. This study presents the first comprehensive checklist of Cortinarius sensu lato in the country, integrating historical records, literature data, field surveys, and molecular data. A total of 231 species is confirmed, including 110 supported by DNA sequence evidence and 121 validated solely based on morphology. Spatial analysis of collection sites highlights two major research hotspots in the Apuseni Mountains and the Transylvanian Basin, reflecting uneven sampling effort. Despite its richness and ecological importance, Romanian Cortinarius remains underrepresented in global sequence repositories. These findings emphasize the need for broader molecular surveys and systematic biodiversity mapping to resolve species boundaries and better integrate Romanian taxa into European and global frameworks. Article history: Received 1 September 2025; Revised 27 November 2025; Accepted 27 November 2025; Available online 20 December 2025